«Fece della sua scienza arma per la libertà»: Ricordo di Gianfranco Mattei (1916-1944) - Calascibetta, Franco (Chimica nella Scuola, 2025)
In early February 1944, Gianfranco Mattei died in a Nazi prison in Rome. Having graduated in chemistry in Florence in 1938, in 1939 he was appointed assistant professor at the Polytechnic of Milan, in the group led by Giulio Natta. In the following years he taught courses in Analytical Chemistry and carried out numerous research projects, documented by 17 publications. After 8 September 1943 he resigned from the Polytechnic and moved to Rome, where he joined the partisan struggle, becoming one of the bomb disposal experts of the GAP, patriotic action groups. Arrested on 1 February, he was taken to Via Tasso and immediately tortured. He died a few days later, almost certainly by suicide, to avoid the risk of compromising his comrades under torture.